326 USE OF A PHARMACY PRIORITISATION TOOLKIT IN FRAIL OLDER ADULTS PRESENTING TO THE EMERGENCY DEPARTMENT. (25th October 2022) - Kennedy, E; Mulvihill, M; Cronin, L; Scannell, M; Coakley, E; Lyons, M; Barrett, L; Cloney, T; Pillay, I
Abstract: Background: A Pharmacy Prioritisation Toolkit (PPT) was adapted for use by a front door frailty multidisciplinary team to direct pharmacist review. Methods: Over a 4-week period pharmacist referrals based on a toolkit used by the team were reviewed. Data was recorded in Excel including age, reason for referral and outcome of Medicines Optimisation Review (MOR). Pharmacy-identified patients were also analysed. Results: Forty-Five patients were referred by the team using the PPT and 25 were pharmacist-identified for review. Reason for referral were use of high-risk medication (20/45), suspected medication related admission (9/45), chronic kidney disease or acute kidney injury (7/45), specific pharmaceutical concerns (5/45) >10 regular medications (4/45). Of those reviewed, 29 MORs were made. Of patients who were pharmacist identified, 10 MORs were made (53% of patients). The toolkit was retrospectively applied to these patients and would have selected all but 3. Conclusion: The PPT was successfully used by the team to generate 45 referrals for pharmacist review over a 4-week period. As a result of analysis of these recommendations, antimicrobial prophylaxis for urinary tract infections will be added to the high-risk medicines list on the PPT. Development of the toolkit is ongoing using a plan, do, study, act model with input from all members of the team to further improve both its efficacy and utility.